Analisis Peramalan Permintaan Jaket Inalcafa pada Produk Pria dengan Metode Double Moving Average - Harun Indra Kusuma; Ridwan Saputra (G-Tech: Jurnal Teknologi Terapan, 2024)
Inalcafa jacket products have three types of variations, including for men, women and children. In this study, researchers tried to predict the number of requests for inalcafa jackets in men's product variations over the next six months. By forecasting the number of requests for Inalcafa jackets, it can provide information on the number of requests for Inalcafa jackets in men's product variations in the next period. The forecasting methods that we calculate include the Double Moving Average method. After the researcher carried out forecasting calculations using the double moving average method, the researcher then determined the upper class limit, middle value and lower class limit based on sales data from the previous 24 months. Finally, the researcher carried out a Moving Range calculation to show the comparison of actual data values with forecasted values. After the researchers carried out forecasting calculations using the double moving average method, an error value of 6.77% was obtained. The predicted production numbers for the next 6 months have an average of 34.67 men's jacket variations produced.